2014
DOI: 10.1016/j.nrl.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Experiencia clínica con los cannabinoides en la terapia de la espasticidad en la esclerosis múltiple

Abstract: THC/CBD appears to be a good alternative to standard treatment as it improves refractory spasticity in MS and has an acceptable toxicity profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The first section assesses knowledge of medical marijuana, including therapeutic uses and adverse effects. Only uses [3] and adverse effects [10][11][12][13][14][15][16][17] of cannabinoid-based medicines authorized in European Union countries were included. The second section measures students' attitudes and opinions regarding medical and recreational use of marijuana and evaluates their confidence levels regarding efficacy, safety and drug interactions of medical marijuana using 23 questions with a five-point Likert scale for each (1 = strongly disagree to 5 = strongly agree).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first section assesses knowledge of medical marijuana, including therapeutic uses and adverse effects. Only uses [3] and adverse effects [10][11][12][13][14][15][16][17] of cannabinoid-based medicines authorized in European Union countries were included. The second section measures students' attitudes and opinions regarding medical and recreational use of marijuana and evaluates their confidence levels regarding efficacy, safety and drug interactions of medical marijuana using 23 questions with a five-point Likert scale for each (1 = strongly disagree to 5 = strongly agree).…”
Section: Data Collectionmentioning
confidence: 99%
“…Sativex, Cesamet, Marinol, etc.) to treat a variety of conditions such as spasticity, chronic pain and others [3,[6][7][8][9], despite the potential for side effects [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…CBD has long lasting effects (up to 80 days) and has been used for the treatment of inflammatory pain and multiple sclerosis (MS) in mouse models (11). In humans CBD treatment safely and effectively reduces symptoms of pain and spasticity in MS patients (12). Additionally, both CBD and Abn-CBD mediate a potentially protective role in diabetes (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Three main active principles derived from cannabis formulate these drugs: dronabinol (Marinol ® ), a synthetic isomer of Δ 9 -THC, nabilone (Cesamet ® ), a synthetic analogue of Δ 9 -THC and nabiximols (Sativex ® ), a 1:1 mix of Δ 9 -THC and CBD [380]. Sativex ® consists of an oral spray approved in some European countries and Canada for the treatment of spasticity and pain relief in MS patients, with mild-to-moderate side effects that occur scarcely in patients [379,380,406,407,408,409,410,411,412,413,414,415,416]. Nevertheless, no trial has shown a slower disease progression in MS patients prescribed with THC-based drugs and, hence, there are still no evidence of its neuroprotective effect in humans [379,417,418].…”
Section: Role Of Cannabinoids In Neurogenesis and Pathophysiologymentioning
confidence: 99%